Utilization of Montmorillonite-Modified Earthenware from Bentonite-Ca as a Microbial Fuel Cell (MFC) Membrane Based on Tempe Liquid Waste as a Substrate - Sudarlin Sudarlin; Andika Wahyu Afrianto; Melly Khoerunnisa; Dhea Wiegya Rahmadhani; Anggit Nugroho (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Modifications of the Microbial Fuel Cell (MFC) membrane need to be carried out to increase its electric potential energy. This research aims to determine the effect of montmorillonite from bentonite-Ca as a composite in modified earthenware (GT), which is then used as a membrane of the MFC-based on tempe wastewater as substrate. The results obtained were compared to MFC that used pure earthenware membrane (GM). The ratio of bentonite-Ca and clay in GT was 50:50, while GM used 100% of clay. Characterizations of GT dan GM were performed using FTIR, XRD, and SAA. MFC testing was carried out for 24 hours, where every 2 hours, measurements of potential difference (V), current (A), and power density (W/cm2) were carried out. FTIR and XRD data showed an increase in montmorillonite content in GT, while SAA data showed a decrease in pore volume in GT. The decrease in pore volume GT occurs due to an increase in the number of trivalent cations (Al3+, Fe3+) and bivalent (Mg2+). These cations help transfer protons from the anode to the cathode, which causes a decrease in the potential difference and an increase in the current strength and the MFC-GT power density. The average difference between the decrease in potential difference from MFC-GM to MFC-GT is 0.043 V, while the increase in current is 0.022 mA, and the increase in power density is 0.163 mW/cm2.